Detection of Acquired Antibiotic Resistance Genes in Domestic Pig (Sus scrofa) and Common Carp (Cyprinus carpio) Intestinal Samples by Metagenomics Analyses in Hungary - Balázs Libisch; Sahabi Abdulkadir; Tibor Keresztény; Péter P. Papp; Ferenc Olasz; Hedvig Fébel; Zsuzsanna J. Sándor; Geertrui Rasschaert; Ellen Lambrecht; Marc Heyndrickx; András Szabó; Melinda Kovács; et al. (MDPI AG, 2022)
The aim of this study was metagenomics analyses of acquired antibiotic-resistance genes (ARGs) in the intestinal microbiome of two important food-animal species in Hungary from a One Health perspective. Intestinal content samples were collected from 12 domestic pigs (Sus scrofa) and from a common carp (Cyprinus carpio). Shotgun metagenomic sequencing of DNA purified from the intestinal samples was performed on the Illumina platform. The ResFinder database was applied for detecting acquired ARGs in the assembled metagenomic contigs. Altogether, 59 acquired ARG types were identified, 51 genes from domestic pig and 12 genes from the carp intestinal microbiome. ARG types belonged to the antibiotic classes aminoglycosides (27.1%), tetracyclines (25.4%), β-lactams (16.9%), and others. Of the identified ARGs, tet(E), a blaOXA-48-like β-lactamase gene, as well as cphA4, ampS, aadA2, qnrS2, and sul1, were identified only in carp but not in swine samples. Several of the detected acquired ARGs have not yet been described from food animals in Hungary. The tet(Q), tet(W), tet(O), and mef(A) genes detected in the intestinal microbiome of domestic pigs had also been identified from free-living wild boars in Hungary, suggesting a possible relationship between the occurrence of acquired ARGs in domestic and wild animal populations.